Re-examining stone circles in Dorset: the results of recent research and non-intrusive surveys at Kingston Russell stone circle. Issue 1 (2nd January 2022) - Rylatt, Jim; Teather, Anne; Pullen, Rebecca; Pinnell, Jodie; Randall, Sam; Roberts, Hayley; Chamberlain, Andrew
ABSTRACT: The Kingston Russell stone circle on Tenants Hill is the largest preserved stone circle in Dorset. Since the Piggotts' summary of the stone and earth circles in Dorset, a great deal has changed in our perceptions and dating of these types of monuments in Britain, but there has been little further research into the stone circles of Dorset. The community archaeology company Past Participate has been working on Tenants Hill since 2018, and this paper reports on our historical and archaeological research on stone circles in south Dorset, and our non-invasive surveys of the Kingston Russell stone circle. We have increased the corpus of potential stone circles in this area to 14, with the majority of these having been destroyed in the last few hundred years. We argue that the landscape placement of the Kingston Russell stone circle has contributed to its survival.